2020
DOI: 10.1007/s42250-020-00122-x
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Detection of Uric Acid with High Sensitivity Using Cu2O@Ag Nanocomposites

Abstract: In this paper, we built the Cu 2 O@Ag nanocomposites-catalyzed 3,3′,5,5′-tetramethylbenzidine (TMB)-H 2 O 2 system for sensitive, rapid, and low-cost colorimetric sensing of uric acid (UA). Firstly, Ag nanotriangles were synthesized by dynamic method, and then Cu 2 O was encapsulated on the nanoflakes to synthesize Cu 2 O@Ag nanocomposites. Characterization of the structure and morphology of nanocomposites material were characterized by transmission electron microscopy, X-ray energy-dispersive spectroscopy, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…On the other hand, it was found that the uricase immobilized on the EGFET biosensor showed a larger V REF than that without uricase, suggesting the presence of a negative charge in the uricase. 46 The sensing mechanism of an electrochemical uric acid biosensor involves an enzymatic reaction catalyzed by uricase, 10…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it was found that the uricase immobilized on the EGFET biosensor showed a larger V REF than that without uricase, suggesting the presence of a negative charge in the uricase. 46 The sensing mechanism of an electrochemical uric acid biosensor involves an enzymatic reaction catalyzed by uricase, 10…”
Section: Resultsmentioning
confidence: 99%
“…9 Because it has a biologically active compound, uric acid is frequently interacted with the uricase on an electrode in an aqueous solution to produce allantoin, H 2 O 2 and CO 2 . 10 Since an ion-sensitive field-effect transistor (ISFET) was introduced by Bergveld 11 for neurophysiological measurements, various sensor devices, such as light-addressable potentiometric sensor (LAPS), extended-gate field-effect transistor (EGFET), nanowire field-effect transistor (FET), electrolyte-insulator-semiconductor (EIS), [12][13][14][15][16] have been developed and employed in different applications in clinical chemistry and laboratory medicine, food industry, industrial process control, environmental control, and chemical and biological warfare agents. Caras and Janata firstly proposed an enzyme FET device based on an ISFET sensor.…”
mentioning
confidence: 99%
“…Biosensors 2021, 11, 287 2 of 14 A variety of methods can be used to measure UA in biological fluids, including fluorescent [6], chromatographic with mass spectrometry, electrochemical and fluorescence detection [1,7,8], enzymatic colorimetric [9], capillary electrophoresis with electrochemical detection [10,11], and electrochemical [12,13]. These methods have both benefits and limitations.…”
Section: Introductionmentioning
confidence: 99%